Cyberanthropology of Network Journalism. Theoretical Approaches and Methodological Proposals for the Study of the Digital Audience - Flores Vivar, Jesús Miguel (2018)
Article analyzes the inclusion of neurosciences such as Anthropology and Ethnography in the study of online audiences. These disciplines, when used in digital environments, derive in names such as cyberanthropology, digital anthropology or virtual ethnography. These acquire relevance in the communicative processes of the people mediated by computer, influenced by the new narrative forms, proposing a more transversal and multidisciplinary approach in the study of users with the aim of knowing and detecting the needs of the same, as well as, knowing in depth the phenomenon of masses that are aligned in social networks using different mobile devices. Finally, some additional steps are suggested for the articulation of Anthropology for Cyberjournalism, exploring the implications of the disciplines treated as innovative strategies in the study of journalism and communication.